LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK DISKUSI UNTUK MEREDUKSI PERILAKU MEMBOLOS SISWA KELAS VIII SMP PGRI NGAMPRAH - Fauziah Hasanah; Teti Sobari; Wiwin Yuliani (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to determine the effectiveness of group guidance services with discussion techniques in overcoming truancy behavior in students. Truancy behavior is defined as a student's absence from school without a valid reason and exceeding the deadline set by the school. This behavior can be caused by a variety of factors, such as economic factors, a lack of responsibility, and environmental influences. Group guidance services with group discussion techniques are one way to help students overcome truancy. This technique is carried out by discussing in group situations continuously and systematically. This study uses a type of mix method with a pre-test post-test group design. The subjects in this study are students of class VIII B SMP PGRI Ngamprah which consists of 8 students. Based on the results of the paired t test with a value of 0.000 < 0.05, it shows that the Ha hypothesis is accepted and Ho is rejected, which means that there is an influence on group guidance services using dusukusi techniques to reduce truancy behavior of students in grade VIII B SMP Pgri Ngamprah. The results of the study show that group guidance services with discussion techniques are effective in overcoming truancy behavior in students. This is evidenced by the increase in student attendance at school after participating in group guidance services. This research also shows that group discussion techniques can help students in developing their motivation to learn and their ability to solve problems.Keywords: Truancy Behavior, Group Guidance, Discussion Techniques